Efektivitas Penyaluran Pembiayaan KPR Subsidi Pada Masyarakat Di Bank Syariah Indonesia KCP Tuban - Akyun, Nadiya Qurota; Rustyawati, Dian (Jurnal Perbankan Syariah, 2024)
This study aims to examine the implementation and effectiveness of the subsidized Home Ownership Loan (KPR) financing program at Bank Syariah Indonesia (BSI) KCP Tuban. This qualitative research with a descriptive approach utilizes data collected through interviews and observations. Data analysis employs descriptive techniques, and data validity is tested using triangulation. Data was gathered through three stages: observation, interviews, and document collection. The findings indicate that the implementation of the subsidized KPR program at BSI KCP Tuban provides satisfactory service during the financing process. The process is easy and transparent, with friendly and informative staff. Moreover, the disbursement of subsidized KPR financing has proven effective in assisting low-income communities in acquiring homes. The process is smooth, with easily understandable requirements and a quick approval process. This demonstrates that subsidized KPR is an effective solution in helping the community meet their housing needs.